The changing face of pastoral systems in grass dominated ecosystems of Eastern Africa - Reid, Robin S.; Serneels, S.; Nyabenge, M.; Hanson, Jean (Food and Agriculture Organization of the United Nations, 2005)
All eastern Africa is in the tropics, but its grasslands cover a very wide range of altitudes. Extensive grasslands are mostly in arid and semi -arid zones. The area is subject to droughts and a high degree of pastoral risk. Potential vegetation is largely desert and semi-desert, bush and woodland, with only a small area of pure grassland, but the grass -dominated herbaceous layer of the other formations is very important for wildlife and livestock; 75 percent of eastern Africa is dominated by grasslands, often with a varying amount of woody vegetation. The grasslands have been grazed by livestock and game for millennia. Eastern Africa is a centre of genetic diversity for grasses. Six to eleven main grassland zones have been described. Grasslands are either under government control, are open access or are common property resources. Access to resources are under national laws but frequently traditional land use rights are granted by local communities. National land tenure systems are unrelated to traditional ones. Governments supported cropping and reduction of communal grazing land; contraction of pastoral systems reduces the scale of resource use by pastoral peoples. The population is very varied - pastoral groups tend to be of different ethnicities from agricultural or agropastoral groups. Most pastoral systems are in the semi-arid areas, with small areas in hyper-arid and subhumid zones. Traditionally, livestock and their products were for subsistence and wealth, but now many are marketed. Grasslands are increasingly being integrated into farming as pastoral systems evolve. Sown forages are widely used in agricultural areas. Cattle, like people, are mostly in the non-pastoral areas (70 percent), except in countries with little high-potential land. Cattle, camels, sheep, goats and donkeys are the main livestock kept by the pastoralists for subsistence; most herds are mixed. Indigenous breeds are the majority, although exotic cattle are kept for dairying in high altitude zones. Wildlife are widespread in the grazing lands and are important for tourism. Agricultural development along watercourses limits access by wildlife and pastoral stock.